Primary cytoreductive surgery with or without hyperthermic intraperitoneal chemotherapy (HIPEC) for FIGO stage III epithelial ovarian cancer: OVHIPEC‐2, a phase III randomized clinical trial. Issue 6 (June 2020) - Koole, Simone; van Stein, Ruby; Sikorska, Karolina; Barton, Desmond; Perrin, Lewis; Brennan, Donal; Zivanovic, Oliver; Mosgaard, Berit Jul; Fagotti, Anna; Colombo, Pierre‐Emmanuel; Sonke, Gabe; van Driel, W J
ABSTRACT : Background : The addition of hyperthermic intraperitoneal chemotherapy (HIPEC) to interval cytoreductive surgery improves recurrence‐free and overall survival in patients with FIGO stage III ovarian cancer who are ineligible for primary cytoreductive surgery. The effect of HIPEC remains undetermined in patients who are candidates for primary cytoreductive surgery. Primary objective : The primary objective is to evaluate the effect of HIPEC on overall survival in patients with FIGO stage III epithelial ovarian cancer who are treated with primary cytoreductive surgery resulting in no residual disease, or residual disease up to 2.5 mm in maximum dimension. Study hypothesis : We hypothesize that the addition of HIPEC to primary cytoreductive surgery improves overall survival in patients with primary FIGO stage III epithelial ovarian cancer. Trial design : This international, randomized, open‐label, phase III trial will enroll 538 patients with newly diagnosed FIGO stage III epithelial ovarian cancer. Following complete or near‐complete (residual disease ≤2.5 mm) primary cytoreduction, patients are randomly allocated (1:1) to receive HIPEC or no HIPEC. All patients will receive six courses of platinum‐paclitaxel chemotherapy, and maintenance PARP‐inhibitor or bevacizumab according to current guidelines. Major eligibility criteria : Patients with FIGO stage III primary epithelial ovarian, fallopian tube, or primary peritoneal cancer are eligible after complete or near‐complete primary cytoreductive surgery. Patients with resectable umbilical, spleen, or local bowel lesions may be included. Enlarged extra‐abdominal lymph nodes should be negative on FDG‐PET or fine‐needle aspiration/biopsy. Primary endpoint : The primary endpoint is overall survival. Sample size : To detect a HR of 0.67 in favor of HIPEC, 200 overall survival events are required. With an expected accrual period of 60 months and 12 months additional follow‐up, 538 patients need to be randomized. Estimated dates for completing accrual and presenting results : The OVHIPEC‐2 trial started in January 2020 and primary analyses are anticipated in 2026. Trial registration : ClinicalTrials.gov:NCT03772028